Clinical determinants of clopidogrel responsiveness in a heterogeneous cohort of Puerto Rican Hispanics. (September 2017) - Hernandez-Suarez, Dagmar F.; Scott, Stuart A.; Tomey, Matthew I.; Melin, Kyle; Lopez-Candales, Angel; Buckley, Charlotte E.; Duconge, Jorge
Background: Clopidogrel is by far the most prescribed platelet adenosine diphosphate (ADP) antagonist in Puerto Rico despite the advent of newer agents (prasugrel and ticagrelor). Given the paucity of data on clopidogrel responsiveness in Hispanics, we sought to determine the association between clinical characteristics and platelet reactivity in Puerto Rican patients on clopidogrel therapy. Study population: A total of 100 Puerto Rican patients on clopidogrel therapy were enrolled and allocated into two groups: Group I, without high on-treatment platelet reactivity (HTPR); and Group II, with HTPR. Platelet function was measured ex vivo using the VerifyNow® P2Y12 assay. Results: The cohort was comprised of Hispanic patients with coronary artery disease (57%), peripheral artery disease (32%), carotid artery stenosis (7%), cerebral artery aneurysm (2%), and stroke (2%). Mean platelet reactivity was 200 ± 61 P2Y12 reaction units (PRUs) (range: 8–324), and 35% of patients had HTPR (PRUs ⩾ 230). Multivariable logistic regression analysis determined that diabetes mellitus (DM) [odds ratio (OR) = 3.27; 95% confidence interval (CI): 1.20–8.96], use of proton-pump inhibitors (PPIs) (OR = 3.60; 95% CI: 1.09–11.82), and calcium channel blockers (CCBs) (OR = 3.10; 95% CI: 1.09–8.83) were independent predictors of HTPR ( p < 0.05) after adjusting for other clinical variables. Conclusions: In a sample of 100 Puerto Rican Hispanic patients on clopidogrel, 35% had HTPR. Furthermore, DM, PPIs and CCBs predicted HTPR. Clinical outcome data are needed to identify appropriate PRU thresholds for risk prediction in the Puerto Rican population.